(untitled) (Journal of Economic Research & Business Administration, 2017)
This article describes the economic development of Kazakhstan since it gained its independence in 1991. Specifically, article draws upon the difficulties Kazakhstan faced in 1990s after the collapse of the Soviet Union. Moreover, the initial reforms of the government, such as introducing own currency, privatisation, creation of National Fund is discussed. Graduallyarticle defines the stages of development of the country during the boom period of the economy starting from 2000s, mainly caused by the high oil prices. On the other hand, author describes about overreliance of the economy on prices of raw materials, leading to signs of Dutch disease. The world economic crisis in 2008 and its influence on Kazakhstani economy, mainly to its currency and banking system is mentioned by analysing country`s macroeconomic indicators. Main goal of this article is to analyse the condition of the economy during this period and measures fulfilled by the government to tackle the challenges that Kazakhstani economy faced in recent years.